Qualitative Study on Chinese Students’ Perception of U.S. University Life - Tang, Xiaokang; Collier, Daniel; Witt, Allison (Journal of International Students, 2018)
This qualitative research was conducted on Chinese international students preparing to study in the United States about their expectation and perception of American universities. It explored motivation for pursuing degrees in the United States, expectations of life in the United States, and plans post-graduation. Findings suggest that these students foresee U.S. classes to be rigorous due to two notable barriers: English proficiency issue and difference in learning environment. Furthermore, the students promoted desires to build relationships with domestic students but already internalized beliefs that this action was unlikely. They presumed that most networking would occur with co-nationals due to comfort and ease. Finally, parental expectations emerged as a significant factor that influence Chinese international students’ desire to study in the United States and post-graduation plans.